The White Man's Burden: Why the West's Efforts to Aid the Rest Have Do ne So Much Ill and So Little: Why the West's Efforts to Aid the Rest H ave Done So Much Ill and So Little Good - Easterly, William (Oxford University Press, 2007)
We are all aware of the extreme hunger and poverty that afflict the wo rld's poor. We hear the facts, see the images on television, buy the T -shirt and are moved as individuals and governments to dig deep into o ur pockets. Yet what happens to all this aid? Why after 50 years and $ 2.3 trillion are there still children dying for lack of twelve cents m edicine? Why are there so many people still living on less than $1 a d ay without clean water, food, sanitation, shelter, education or medici ne? In The White Man's Burden William Easterly, acclaimed author and f ormer economist at the World Bank, addresses these twin tragedies head on. While recognising the energy and compassion behind the campaign t o make poverty history he argues urgently and powerfully that grand pl ans and good intentions are a part of the problem not the solution. Gi ving aid is not enough, we must ensure that it reaches the people who need it most and the only way to make this happens is through accounta bility and by learning from past experiences. Without claiming to have all the answers, William Easterly chastises the complacent and patron ising attitude of the West that attempts to impose solutions from abov e. In this book, which is by turns angry, moving, irreverent but alway s rigorous, he calls on each and everyone of us to take responsibility , whether donors, aid workers or ordinary citizens, so that more aid r eaches the people it is supposed to help, the mother who cannot feed h er children, the little girl who has to collect firewood rather than g o to school, the father who cannot work because he has been crippled b y war.